2014
DOI: 10.1101/sqb.2014.79.024794
|View full text |Cite
|
Sign up to set email alerts
|

The Brainstem Oscillator for Whisking and the Case for Breathing as the Master Clock for Orofacial Motor Actions

Abstract: Whisking and sniffing are predominant aspects of exploratory behavior in rodents. We review evidence that these motor rhythms are coordinated by the respiratory patterning circuitry in the ventral medulla. A recently described region in the intermediate reticular zone of the medulla functions as an autonomous whisking oscillator, whose neuronal output is reset upon each breath by input from the preBötzinger complex. Based on similarities between this neuronal circuit architecture and that of other orofacial be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…What might be the utility of coordinating the fast, rhythmic motion of the different sensory apparatuses as animals explore their nearby environment? It is an open issue whether the coordination of these motor actions maximizes sensory input [30, 31], such as by sweeping odorants toward the nose. Any source of sensory input that contributes to both touch and olfaction, which are elements of social interactions [32] as well as exploration (Figure 4G), will lead to multisensory input that is likely to be phase-locked to breathing.…”
Section: Discussionmentioning
confidence: 99%
“…What might be the utility of coordinating the fast, rhythmic motion of the different sensory apparatuses as animals explore their nearby environment? It is an open issue whether the coordination of these motor actions maximizes sensory input [30, 31], such as by sweeping odorants toward the nose. Any source of sensory input that contributes to both touch and olfaction, which are elements of social interactions [32] as well as exploration (Figure 4G), will lead to multisensory input that is likely to be phase-locked to breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cranial nerves are required to dilate or stiffen the nasopharyngeal, oropharyngeal and laryngeal airways maintaining their patency (Abdala et al., ; de Britto & Moraes, ; St‐John, Rudkin, & Leiter, ). Indeed, several studies demonstrated that breathing modulates the nasofacial and oral motor outflows in rats (Kleinfeld, Moore, Wang, & Deschênes, ). Breathing has not only its physiological role in blood gas homeostasis but also serves as a common clock that couples nasofacial and oral senses during exploratory behaviours such as sniffing (Kleinfeld, Deschênes, Wang, & Moore, ).…”
Section: Introductionmentioning
confidence: 99%
“…The slow, orienting movements of the nose likely play a role in olfactory navigation since lateral deflections affect air flow between sides of the nasal cavity (Deschênes et al 2016a) and bilateral comparisons improve trail-tracking (Duistermars et al 2009;Louis et al 2008;Martin 1965;Porter et al 2007;Steck et al 2010). Synchronization of movement on a breath-bybreath cycle is seen in many types of orofacial movement and may play a role in binding multimodal sensory inputs (Heck et al 2017;Kepecs et al 2006;Kleinfeld et al 2014aKleinfeld et al , 2014bMoore et al 2013;Ranade et al 2013;Sirotin et al 2014;Wachowiak 2011;Welker 1964).…”
Section: Introductionmentioning
confidence: 99%